Literature Review: Konsep Smart Port di Indonesia dengan Metode Analisis Bibliometrik - Nur Azisah; Chairul Paotonan; Muhammad Asdar (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Smart Port is a trending solution to meet the challenges of the maritime industry. "Smart" ports mean more attractive and competitive for customers. Artificial intelligence such as the Internet of Things, Big Data, and other technologies allow ports to create smarter workflows, conditions, or customer management, helping to make better decisions so that they can operate more effectively. This research applies bibliometric analysis. Bibliometric analysis is a literature review method that is widely applied in the field of business review to reveal the development of a field of research. This study reviewed 87 studies related to Smart Port research in Indonesia published between 2013 and 2023. Based on this research, the Smart Port Concept developed in Indonesia in terms of technology use includes automated operations using technology systems to control equipment, thereby minimizing human error, by digitizing gateways and using the Internet of Things (IoT). In the environmental concept, an environmental management system is needed to preserve the environment by adapting the concepts of sustainability and green port. This study contributes to a better understanding of the smart Port concept, which lacks an exact definition. Furthermore, this study provides an overview of publication trends and distribution, influential publishers, as well as the Smart Port concepts that are widely adopted in Indonesia. Regarding industry contributions, the results of this study will help port stakeholders clearly understand the issues related to smart port development to make critical decisions in applying advanced technologies to enhance smart port development and high efficiency in port operations.